2021
DOI: 10.3389/fonc.2021.557477
|View full text |Cite
|
Sign up to set email alerts
|

Unraveling Heterogeneity of Tumor Cells and Microenvironment and Its Clinical Implications for Triple Negative Breast Cancer

Abstract: Objective: Triple negative breast cancer (TNBC) is an aggressive subtype of breast cancer, characterized by extensive intratumoral heterogeneity. We aimed to systematically characterize the tumor heterogeneity of TNBC.Methods: Single-cell RNA sequencing (scRNA-seq) of TNBC cells were obtained from the GSE118389 and GSE75688 datasets. After integration of the two datasets, cell clustering analysis was performed using the Seurat package. According to the marker genes of cell cycle, cell cycle of each cell cluste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(21 citation statements)
references
References 30 publications
1
20
0
Order By: Relevance
“…Macrophages are typically subclassed within the TIME as classically activated, anti-tumour M1-or alternatively activated, pro-tumour M2-like macrophages, also known as tumour associated macrophages (TAMs). Higher proportions of CD68 + macrophages are seen in TNBC compared to hormone-positive disease, with higher reported unpolarised M0-and M1-like subtype proportions [44][45][46] . However, further studies have shown that TNBC may selectively cause unpolarised macrophages to become TAMs, and thus other studies have shown TAMs to be in greater proportions 47,48 .…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Macrophages are typically subclassed within the TIME as classically activated, anti-tumour M1-or alternatively activated, pro-tumour M2-like macrophages, also known as tumour associated macrophages (TAMs). Higher proportions of CD68 + macrophages are seen in TNBC compared to hormone-positive disease, with higher reported unpolarised M0-and M1-like subtype proportions [44][45][46] . However, further studies have shown that TNBC may selectively cause unpolarised macrophages to become TAMs, and thus other studies have shown TAMs to be in greater proportions 47,48 .…”
Section: Discussionmentioning
confidence: 97%
“…adjuvant or neoadjuvant) seems to have no effect on the prognostic significance, increasing the value macrophages may have as a clinical biomarker. Single cell RNA-sequencing has found smaller proportions of TAMs within the TIME of TNBC, however high expression of the M2 subtype is associated with poorer overall survival (p = 0.002) 46 . An analysis of metastatic TNBC found non-response to neoadjuvant nab-paclitaxel and pembrolizumab resulted in a lower CD68 signature with higher CSF1R-expressing TAMs 62 .…”
Section: Discussionmentioning
confidence: 99%
“…The tumor microenvironment (TME) has been identified playing a critical role in tumor heterogeneity, but the mechanism has not been fully elucidated. Emerging evidence demonstrated that the TME comprises endothelial cells, fibroblasts, immune cells, and extracellular components that contribute to tumor heterogeneity ( Jiang et al, 2021 ; Yuan et al, 2021 ). According to the characteristics of TME, BC was classified into different TME clusters ( Xiao et al, 2019 ).…”
Section: Introductionmentioning
confidence: 99%
“…Since intratumoral heterogeneity and the presence of phenotypically distinct tumor cells within a single tumor is critical to cancer progression and resistance to therapy, understanding the molecular mechanisms underlying the intratumor phenotypic heterogeneity is key for therapeutic targeting of TNBC [9].…”
Section: Introductionmentioning
confidence: 99%